Blue Carbon Ecosystems in Brazil: Overview and an Urgent Call for Conservation and Restoration - Soares, Marcelo O.; Bezerra, Luis Ernesto Arruda; Copertino, Margareth; Lopes, Beatriz Diniz; Barros, Kcrishna Vilanova de Souza; Rocha-Barreira, Cristina Almeida; Maia, Rafaela Camargo; Beloto, Natalia; Cotovicz, Luiz C. (Frontiers in Marine Science, 2022)
In this article, we discuss knowledge and gaps regarding blue carbon ecosystems (BCEs) in Brazil, considering the urgency to apply protection actions and policies to safeguard their biodiversity and associated ecosystem services. We also indicate areas of further research to improve carbon stocks and sequestration rate estimates. We call attention to the shortage of studies on Brazilian BCEs relative to the growing knowledge on the Blue Carbon Framework accumulated worldwide over the last decade. Considering the extensive Brazilian Economic Exclusive Zone (known as “Blue Amazon”), knowledge concerning blue carbon stocks is vital at regional and global scales for mitigating global increases in atmospheric carbon dioxide (CO2). The Blue Amazon has at least 1,100,000 ha of vegetated and non-vegetated coastal ecosystems (mangroves, salt marshes, seagrass meadows, and hypersaline tidal flats) that collectively contain vast amounts of stored carbon, making Brazil an ideal place to test mechanisms for evaluating, conserving, and restoring BCEs. Other poorly understood potential sinks and sources of carbon are macroalgal and rhodolith beds, mudflats, continental shelf sediments, and marine animal forests in shallow, mesophotic, and deep waters. The carbon fluxes between diverse environmental compartments, such as soil–air, soil–water, groundwater–water–surface water, air–water, and land–ocean, in BCEs across the Blue Amazon must be studied. We emphasize the importance of assessing the total carbon stock and the recent dismantling of environmental laws that pose great risks to these important BCEs. The conservation and recovery of these areas would enhance the carbon sequestration capacity of the entire country. Furthermore, we highlight priorities to improve knowledge concerning BCEs and their biogeochemical cycles in the Blue Amazon and to provide information to assist in the reduction of atmospheric levels of CO2 for the United Nations Decade of Ocean Science (2021–2030).